ANALISIS PENGARUH DEAD ENDORSER TERHADAP BRAND PERSONALITY PADA IKLAN KOMPAS DI TELEVISI - Sri Kussujaniatun (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2007)
The objective of this study is to examine : (a) the simultaneous effects of expertise, trustworthiness, and attractiveness on the brand personality, (b) the partial effect of expertise, trustworthiness, and attractiveness on the brand personality, (c) is trustworthiness a dominant variable that effect on the brand Personality The result show that simultaneously, expertise, trustworthiness, and attractiveness on the brand personality. The result also indicat that partially, expertise, trustworthiness, and attractiveness on the brand personality a dominant variable that effect on the brand Personality Keywords: Expertise, Trustworthiness, And Attractiveness On The Brand Personality